Military communications : a test for technology - Bergen, John D. (United States Army in Vietnam, 1986)
In Military Communications: A Test for Technology, John D. Bergen develops the thesis that burgeoning technology in communications faced a severe test in Vietnam. He analyzes the advantages and drawbacks of new communications systems and the effects these systems had on decision making and on command. In doing so, he describes the difficulties that communications systems had in keeping pace with the information explosion and shows that command and control do not necessarily improve with enhanced communications. The book illustrates that the communicator₂s missions of ₃getting the message through₄ was not only critical to the success of combat operations, but also as challenging as combat itself. Bergen₂s clear understanding and description of these issues make this a valuable work for those responsible for the future success of command, control, communications, and intelligence.